Multiplex measurement of proinflammatory cytokines around miniscrews during orthodontic treatment - Camarena Fonseca, Alexandra (2022)
Objective: To determine the levels of proinflammatory cytokines around miniscrews with and without loading, used during orthodontic treatment. Material and Methods: A descriptive longitudinal study was executed with a sample of ten miniscrews inserted in patients that attended a dental clinic. Saliva and peri-implant crevicular fluid samples were taken: at baseline (T0), 24 hours after insertion (T1), 1 week after insertion (T2), 24 hours after loading (T3). The samples obtained were processed by immunoassay and read with a flow cytometer. Results: Data analysis was performed using the SPSS program version 21.0. To verify normal distribution, Kolmogorov-Smirnov test was used, followed by ANOVA to compare and determine statistical significance. Levels of inflammatory mediators in the peri-implant crevicular fluid at T1 had the following order of average values: IL-8>IL-1β >IL-6>TNF-α>IL-10>IL-12p70. Higher values were found 24 hours post-insertion. Salivary levels found were lower but the previously mentioned order was maintained. Statistically significant intergroup differences were found for IL-1β and IL-8 in the peri-implant crevicular fluid. The Scheffe post hoc test showed that there were no statistically significant differences when making an intragroup pair comparison of each mediator level in a given evaluation time. No statistically significant differences were found in saliva inter and intra-group for all the evaluated inflammatory mediators. Conclusions: The miniscrew loading did not generate an increase of the concentrations of the cytokines greater than the effect caused by the insertion per se. The highest levels of inflammatory mediators were found 24 hours post-insertion of the miniscrew.